Advanced oxidation protein products levels and Paraoxonase 1(Arylesterase) activity in patients with thyrodisim - Abdul Latif Jouad, Hadeel; AL- Shammaree , Shatha Abdul Wadood (Journal of Contemporary Medical Sciences, 2023)
Objectives: The purpose of study was to explore the correlation of advanced oxidation protein products (AOPP), which reflect the oxidation of protein and the oxidative stress status, and the activity of antioxidant enzyme of Paraoxonase (PON1), using its arylesterase activity in patients with thyrodisim. Methods: The study included 100 women with newly diagnosed thyrodisim were subdivided in two groups according to thyroid hormones levels: hyperthyroidism group (50 female patients, age range 18-60 years); and hypothyroidism group (50 female patients, age range 18-75 years). A control group (30 healthy females, age range 18–70 years) was also included for comparison. Demographic and clinical measurements for all participants were recorded which include: Body mass index (BMI), age, weight, height, lipid profile, vitamin D, thyroid hormones (TSH, T3, and T4, FT3, FT4), AOPP levels, and arylesterase activity. Results: The serum level of AOPP in hypothyroidism group (71.92±19.04 μmol/L) and in hyperthyroidism group (30.41±4.72 μmol/L) were significantly higher than controls (13.12±2.50 μmol/L) (P<0.05). In contrast, lower aryl esterase activity was found in hypothyroidism (5.03±0.50 U/L), and hyperthyroidism (3.64±0.40 U/L) when compared to control group (6.78±0.62 Ku/L) with significant values (P< 0.05). Conclusions: these results disclosed a significant role of protein oxidation in patients with hypothyroidism as well as the oxidative stress status.